Approved budget estimates for 1989: including the military administrators budget speech. - State Government of Ogun, Nigeria; State Government of Ogun, Nigeria (Abeokuta: State Government of Ogun, Nigeria, 1989)
This volume includes Ogun State approved budget estimates for the 1989 as well as the budget speech by the military administrator Navy Captain M. A. Lawal.
lje 19/3/2019
Arch.
Keywords: Budget; Finance, public; Nigeria